2017
DOI: 10.1111/pre.12172
|View full text |Cite
|
Sign up to set email alerts
|

High morpho‐anatomical variability in Halimeda macroloba (Bryopsidales, Chlorophyta) in Thai waters

Abstract: Halimeda macroloba is a common widespread and morphologically variable species in the Indo-Pacific Ocean. A series of morphometric data (16 morphological and 46 anatomical variables) and the chloroplast-encoded tufA gene were examined to explore the morphological and genetic variations within the species and to better determine species boundaries in H. macroloba in Thai waters. Moreover, the environmental conditions, which may affect morphological variations in H. macroloba, especially of Haplotype I were exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…In fact, because it was totally removed by prior accounting for size differences among segments, the variation in symmetrized segment shapes between populations was completely derived from their static allometry. Varying irradiation among habitats has been identified as one of the factors leading to size variation in Halimeda segments and thalli [ 17 , 19 , 21 , 58 ]. This might have been reflected in our results, as H .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, because it was totally removed by prior accounting for size differences among segments, the variation in symmetrized segment shapes between populations was completely derived from their static allometry. Varying irradiation among habitats has been identified as one of the factors leading to size variation in Halimeda segments and thalli [ 17 , 19 , 21 , 58 ]. This might have been reflected in our results, as H .…”
Section: Discussionmentioning
confidence: 99%
“…Verbruggen and collaborators showed that "deviant segments" with shapes significantly deviating from taxonomic description of their respective species effectively prevent unambiguous morphometric classification of the segments into individual taxa [ 16 ]. Several studies also illustrated that variation of the segments is related to various environmental factors within the marine sublittoral habitats [ 17 – 19 ]. It has been shown that the size of Halimeda segments is often negatively correlated with high irradiation levels typical for shallow habitats close to the sea surface [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The correlation of H. opuntia with environmental factors is relatively low in comparison to H. macroloba , which shows high eigenvalues and responses to many environmental conditions, such as light intensity, depth and substrate type (Pongparadon et al . ). A compact thallus with ribbed reniform segments was found in highly irradiated conditions, and in shade conditions, especially under rocks or coral in the subtidal zone, the thalli changed to lax branching, such as a network with deeply trilobed lower segments and ribbed reniform or tripartite upper segments.…”
Section: Discussionmentioning
confidence: 97%
“…The variations within the H. opuntia species were low compared to those in other Halimeda species. H. opuntia has only two morphs and showed plasticity in only the morphological variations in thallus and segment size and shape, while Halimeda macroloba has more morpho-anatomical variability that is affected by water depth and light in terms of several characteristics, such as holdfast type, segment size and shape, peripheral utricle patterns as seen from the surface view, layers of utricles and shapes of the primary utricle (Pongparadon et al 2017). In addition, Halimeda heteromorpha is another species that has high variation within the species.…”
Section: Species Boundaries and Variations Among Speciesmentioning
confidence: 99%
“…The segments themselves are usually also highly variable within and among individuals of the same species. This variation is related to their position on the thallus [7], which may also be caused by environmental heterogeneity [8][9][10]. Recently, it has been shown that morphological variation of H. tuna segments is tightly constrained by the allometric size-to-shape relation [11].…”
Section: Morphometric Analysis Of Surface Utriclesmentioning
confidence: 99%